A longitudinal study of the association between breast-feeding and harmful oral habits - Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Orlando [UNESP]; Lolli, Luiz Fernando; Garbin, Cléa Adas Saliba [UNESP]; Garbin, Artênio José Ísper [UNESP]; Saliba, Nemre Adas [UNESP] (My University, 2012)
Purpose: The purpose of this paper was to study the pattern of breast-feeding and harmful sucking habits (pacifier- and thumb-sucking) from birth to 12-months-old. Methods: A prospective cohort study with 80 newborn infants and their mothers was conducted. A semi-structured questionnaire on breast-feeding and pacifier- and thumb-sucking behavior was administered during monthly household visits. Data were analyzed using the chi-square test. Results: Exclusive breast-feeding occurred in 50%of infants from birth while 69%of participants were completely weaned by 12-months-old. Pacifier-sucking was more prevalent than thumb-sucking and was maintained at a higher rate than thumb-sucking throughout the study. The incidence of thumb-sucking was highest between the third and sixth month of life. There was a significant association between a low rate of breast-feeding and pacifier-sucking at the 12-month visit (chi-square=5.29; P<.05). Thumb-sucking did not significantly correlate with breast-feeding behavior. Conclusion: The rate of exclusive breast-feeding was lower than that recommended by the World Health Organization. More than half the infants had a pacifierand /or thumb-sucking habit during the study, and the incidence of breast-feeding was lower in those who used a pacifier.
Keywords: Breast-feeding; Oral habits; Pacifier use; Thumb-sucking